A fast and highly selective Congo red adsorption material based on a cadmium-phosphonate network. Issue 12 (19th June 2019) - Ai, Jing; Tian, Hong-Rui; Min, Xue; Wang, Zi-Chuan; Sun, Zhong-Ming
Abstract : This cadmium-phosphonate network exhibited rapid and efficient adsorption of Congo red dye, as well as excellent structural stability and adsorptive recyclability. Abstract : In this work, a cadmium-phosphonate network was prepared based on a tetrahedral shaped tetraphosphonic acid linker. The resulting three-dimensional compound Cd4 (H4 L)2 (phen)2 (H2 O)4 (1 ) exhibited a rapid and efficient adsorption of Congo red (CR) dye, the adsorption capacity of which reached 684 mg g −1 . Furthermore, this adsorbent showed excellent structural stability and adsorptive recyclability after three times of adsorption and desorption. The absorption kinetics fitted well with the pseudo-second-order kinetic model, revealing that the adsorption of the cadmium-phosphonate compound undergoes a chemical process, where hydrogen bonding between the amide groups (from CR) and the uncoordinated phosphonate oxygen atoms of the compound plays a pivotal role.